Fixed-time sliding mode control based plant/controller co-design of dual-motor driving system - Zeng, Tianyi; Ren, Xuemei; Zhang, Yao (International journal of systems science, 2019)
A fixed-time sliding mode controller based plant/controller co-design scheme is developed for dual-motor driving systems. The proposed controller is fixed-time stable subject to unknown disturbances which guarantees the robustness of the proposed control scheme and a less conservative solution can be ensured by comparing with the conventional fixed-time convergence technique. Due to the existence of couplings between the plant and the controller, traditional design procedures in which the plant and the controller are designed sequentially and separately cannot guarantee the overall optimum of control systems. A co-design scheme based on the nested optimisation strategy is developed in this paper. With the nested optimisation strategy, the co-design solution can be achieved efficiently and reliably. A combined cost function considering both the plant and the controller is developed so that the largest load can be achieved without degrading the control performance. The fixed-time convergent controller is employed and considered into the co-design scheme. The gravitational search algorithm is adopted to optimise controller parameters in the co-design scheme. With the presented co-design method, the largest load of the studied system can be achieved with the satisfactory control performance. Contrastive Simulation and experimental results demonstrate the efficacy of the proposed controller and co-design scheme.